Hyperventilation echocardiography in INOCA: the HEROIC study. (25th November 2020) - Boskovic, N; Djordjevic-Dikic, A; Dedic, S; Giga, V; Nedeljkovic, I; Tesic, M; Jovanovic, I; Aleksandric, S; Beleslin, B; Picano, E
Abstract: Background: Patients with ischemia and no obstructive coronary artery disease (INOCA) are a heterogeneous group and an unmet diagnostic challenge. Noninvasive Doppler is a feasible tool to assess coronary flow velocity (CFV) in left anterior descending coronary artery (LAD) during stress echocardiography (SE). Aim: To assess CFV response during coronary vasoconstrictor and vasodilator stimuli in INOCA patients. Methods: In a prospective single center study, we enrolled 16 INOCA patients (age 60±12 years, 15 females) with previously normal angiograms. All underwent SE testing with hyperventilation (HYP, respiratory rate of 30 per min for 5') followed by supine bicycle exercise (HYP+EXE); and adenosine CFV evaluation (ADO, 0.84 mg/kg in 1 min) on the other day. The ratio of peak/rest changes of CFV during HYP in LAD was taken as an index of vasoconstriction, and CFV reserve was evaluated after EXE. An abnormal response to HYP was a CFV ratio <1.0 (vasoconstrictor response). An abnormal response to ADO was a CFV reserve <2.0 (blunted vasodilatory response). CFVR at peak HYP+ EXE was an indicator of endothelial dependent vasodilatation. Results: The double product increased during HYP, in comparison to rest (13 337 vs 9858, p<0.001), and further increase with EXE (21 118 vs HYP, p<0.001). Chest pain or dyspnea were present in 2/16 pts during HYP, and in 5/16 patients during HYP+EXE (12.5% vs 31.25%, p=0.083). ST segment depression (≥1mm) was present in 1/16 patients during HYP, and 3/16 during HYP+EXE. Two patients showed regional wall motion abnormalities with HYP+EXE. CFVR response was blunted in 9/16 patients during HYP+EXE, and abnormal for vasoconstriction during HYP in 6. Vasodilation during ADO was preserved in all patients. There was significant difference between CFVR response during HYP+EXE and ADO (1.9±0.5 vs 2.4±0.4 respectively, p=0.039), and between CFVR HYP and ADO (1.2±0.3 vs 2.4±0.4, p<0.001). Conclusion: In INOCA patients, HYP+EXE is a more powerful ischemic stress than HYP alone and unmasks abnormalities in regional wall motion and/or CFV response in over one- half of patients, likely unmasking the underlying abnormal coronary vasomotor response of large epicardial and/ or small coronary vessels. INOCA patients show profound heterogeneity of coronary vasomotor responses which can be detected with a combined vasodilator - vasoconstrictor SE approach with CFV assessment. The clarification of underlying coronary microcirculatory heterogeneity is the prerequisite for a personalized treatment, and can be easily extracted from CFV-SE. Normal INOCA hearts are all alike, every abnormal heart is abnormal in its own way. Funding Acknowledgement: Type of funding source: None